Application of Targeted Next-Generation Sequencing in Bronchoalveolar Lavage Fluid for the Detection of Pathogens in Pulmonary Infections - Dai X; Xu K; Tong Y; Li J; Dai L; Shi J; Xie H; Chen X (Infection and Drug Resistance)
Xianning Dai,1 Kai Xu,1 Yu Tong,1 Jing Li,2 Liya Dai,1 Jianyou Shi,1 Haibin Xie,3 Xi Chen3 1Department of Clinical Laboratory, Wenzhou People’s Hospital, Wenzhou Maternal and Child Health Care Hospital, Zhejiang, People’s Republic of China; 2Department of PCCM, Wenzhou People’s Hospital, Wenzhou Maternal and Child Health Care Hospital, Zhejiang, People’s Republic of China; 3Department of Immunization Planning, Prevention and Health Care, Centers for Disease Control of Luchen, Zhejiang, People’s Republic of ChinaCorrespondence: Xi Chen, Department of Immunization Planning, Prevention and health care,Centers for Disease Control of Luchen, No. 3320 Guojing Road, Wenzhou, Zhejiang, 325005, People’s Republic of China, Tel +86 577 56760657, Fax +86 577 56760654, Email cxbrook0577@163.comObjective: This study aims to evaluate the utility of targeted next-generation sequencing (tNGS) in bronchoalveolar lavage fluid (BALF) for hospitalized patients with pulmonary infections.Methods: A cohort of 358 patients who received diagnosis and treatment for respiratory infections in the department of Respiratory Medicine at Wenzhou People’s hospital from January 2023 to April 2024 were selected for this study. The BALF of the patients was analyzed using tNGS, and the diagnostic efficacy of tNGS was subsequently compared with that of conventional testing methods (CTs) for pathogen detection.Results: Through the analysis of tNGS from the cohort, the pathogen detection rate in BALF using tNGS was significantly higher than that of CTs (90.22% VS 57.26%, P=0.001). Among them, Tropheryma Whipplei (6.15%), Bordetella pertussis (2.51%), Non-tuberculous mycobacteria (1.96%), Mycobacteria tuberculosis (1.40%), Chlamydia pneumoniae (1.96%), Chlamydia psittaci (0.56%), Legionella pneumophila (0.28%) were detected using tNGS alone, and the CTs results of these microorganisms were all negative. Among the various types of mixed infections observed, concurrent presence of bacteria and viruses was the most common, accounting for 37.15%. The detection rates of tNGS and CTs have statistical significance (66.87% VS 35.12%, P=0.001). Furthermore, a total of 61 cases of antimicrobial resistance genes were detected, including 34 cases of 23S rRNA A2063G, 6 cases of KPC, 5 cases of OXA, 2 cases of CTX-M, 3 cases of IMP, 1 case of NDM and 13 cases of mecA. Using the clinical diagnosis as references, the positive coincidence rate of the tNGS was significantly higher compared to that of the CTs (P=0.012).Conclusion: Compared to CTs, the application of tNGS enables the identification of a greater diversity of organisms and exhibits superior accuracy, effectively identifying pathogens that are undetectable by CTs, especially fastidious and atypical organisms. Consequently, it holds immense potential in pathogen diagnosis and offers valuable clinical guidance for patients with pulmonary infections.Keywords: bronchoalveolar lavage fluid, targeted next-generation sequencing, pneumonia, pathogen, culture, antimicrobial resistant